Priest, politician, collaborator : Jozef Tiso and the making of fascist Slovakia - Ward, James Mace (Cornell University Press, 2013)
"For God and our homeland," 1887-1918 -- Turning national and political, 1918-19 -- "For God and nation," 1919-25 -- The failure of "activism," 1925-33 -- The lure of the world, 1933-38 -- Standing up for the truth, 1938-39 -- Sacred convictions, 1939-44 -- Losing battles, 1944-2008